Cross-Species Intimacies from Guide Dogs to Artificial Meat: Review of Susan McHugh, Animal Stories: Narrating across Species Lines - Armbruster, Karla (Humanimalia, 2012)
Susan McHugh, Animal Stories: Narrating across Species Lines. Minneapolis, MN: U of Minnesota P, 2011. 280 pp. 25.00 pb.